2012
DOI: 10.3109/08958378.2011.647413
|View full text |Cite
|
Sign up to set email alerts
|

Biological responses in rats exposed to cigarette smoke and Middle East sand (dust)

Abstract: Respiratory symptoms are frequently reported in personnel deployed to the Middle East. This project characterized the respiratory toxicity of inhaled Iraqi sand (IS). Adult rats underwent a 6-wk inhalation to air or mainstream cigarette smoke (MSCS) (3 h/d, 5 d/wk) that included exposure to IS or crystalline silica (1 mg/m(3), 19 h/d, 7 d/wk) or air during the last 2 weeks. Assessments included motor activity, whole-body plethysmography, cytological and biochemical analysis of bronchoalveolar lavage fluid, lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…These results suggest that the exacerbation of pneumonia by desert dust was due to the enhanced production of pro-inflammatory mediators via activation of TLR2 and NALP3 inflammasome pathways in alveolar macrophages [149]. Many study results suggest that the allergic inflammation aggravated by mineral dust may be due to mineral elements (mainly SiO 2 ), and thus the biological effects of desert dust approximate those of silica [138,150,151]. Dust sampled from different sites over the world is dominated by silicon dioxide (SiO 2 ) and aluminum oxide (Al 2 O 3 ).…”
Section: Pathogeny Of Desert Dust On Respiratory Diseasesmentioning
confidence: 94%
“…These results suggest that the exacerbation of pneumonia by desert dust was due to the enhanced production of pro-inflammatory mediators via activation of TLR2 and NALP3 inflammasome pathways in alveolar macrophages [149]. Many study results suggest that the allergic inflammation aggravated by mineral dust may be due to mineral elements (mainly SiO 2 ), and thus the biological effects of desert dust approximate those of silica [138,150,151]. Dust sampled from different sites over the world is dominated by silicon dioxide (SiO 2 ) and aluminum oxide (Al 2 O 3 ).…”
Section: Pathogeny Of Desert Dust On Respiratory Diseasesmentioning
confidence: 94%
“…The distribution of elements in the Ir dust resembles that of the Ku dusts (Table 1), and while measurements of the content of the Camp Victory soil used by Dorman et al, (2012) were not presented, the composition of Camp Victory soil and ambient dust is similar (Engelbrecht et al 2009a; 2009b). The dusts also appear to have a large clay mineral component based on mineralogical analysis (Engelbrecht et al 2009a; 2009b) and elemental composition (National Institute of Science and Technology 2012).…”
Section: Discussionmentioning
confidence: 88%
“…In the first, rats were exposed to settled dust collected at Camp Buehring in northern Kuwait (Wilfong et al 2011) by intratracheal (IT) instillation, and in the second, rats received a whole-body exposure for 2 wk using aerosolized milled surface soil collected at Camp Victory, Baghdad, Iraq (Dorman et al 2012). Neither study found marked pathological effects as a result of exposure.…”
mentioning
confidence: 99%
“…In part 1, dogs were trained to discriminate between AN and a nylon mesh blank. In part 2 the dogs discriminated between AN and a 5 g soil sample collected from Camp Victory Iraq (see Dorman et al, (2012) for additional details about the soil sample). In part 3, the dogs were trained to discriminate between AN and amyl acetate, a chemical with a marked banana odor.…”
Section: An Olfactory Discrimination Testmentioning
confidence: 99%